PENGEMBANGAN USAHA KULINER HOME INDUSTRI SEBAGAI PELUANG KAUM PEREMPUAN MENUJU INDUSTRI KREATIF - Khairil Hamdi; Dorris Yadewani (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
Towards the creative industry today economic activities are forced to intensify information and creativity by relying on ideas and knowledge from human resources as the main key in moving economic activities, housewives and women generally become the main guard in community life to regulate and cultivate the family economy. In fact, housewives have not been able to exploit their potential to help the family economy due to various factors. This community service activity is focused on empowering home industry actors in helping to increase family income, while the problems faced are (1) Lack of knowledge about home industry, 2) Low understanding of the perpetrators of home industry about the importance of the internet to support business activities. The aim of this program is to develop business carried out by groups of housewives to become economically independent communities.